Quantitative Assessment of Thyroid, Submandibular, and Parotid Glands Elasticity With Shear-Wave Elastography in Children. Issue 2 (June 2018) - Arioz Habibi, Hatice; Memis Durmaz, Emine Sebnem; Qarayeva, Vusale; Kandemirli, Sedat Giray; Kalyoncu Ucar, Ayse; Aslan, Mine; Apaydin, Gozde; Kurugoglu, Sebuh; Adaletli, Ibrahim
Abstract : Abstract: Tissue elasticity is becoming a more commonly used parameter in evaluation of parenchyma in inflammatory diseases. Considering the changes in the thyroid and salivary glands with adolescence, determination of mean elasticity ranges with a function of age is necessary to apply ultrasound elastography more widely in the pediatric population. The thyroid, submandibular, and parotid glands of 127 healthy volunteers (66 males, 61 females; mean age = 10.3 ± 3.9 years; range = 3–17 years) were evaluated with shear-wave elastography. The mean elasticity values for the thyroid, submandibular, and parotid glands were 14.6 ± 3.3, 11.8 ± 2.2, and 11.8 ± 2.6 kPa, respectively. There was a significant positive correlation between age and elasticity of the thyroid, submandibular, and parotid glands. There was a significant correlation between age and elasticity value of the thyroid gland adjusted for weight and height. This study provided the baseline quantitative elasticity measures of thyroid, submandibular, and parotid glands, which would be a reference for upcoming studies. In addition, an increase in elasticity value in thyroid gland as a function of age independent of change in weight and height was demonstrated.